MicroRNA-3162-5p-Mediated Crosstalk between Kallikrein Family Members Including Prostate-Specific Antigen in Prostate Cancer. (1st June 2019) - Matin, Farhana; Jeet, Varinder; Srinivasan, Srilakshmi; Cristino, Alexandre S; Panchadsaram, Janaththani; Clements, Judith A; Batra, Jyotsna
Abstract: BACKGROUND: MicroRNAs mediate biological processes through preferential binding to the 3′ untranslated region (3′ UTR) of target genes. Studies have shown their association with prostate cancer (PCa) risk through single-nucleotide polymorphisms (SNPs), known as miRSNPs. In a European cohort, 22 PCa risk-associated miRSNPs have been identified. The most significant miRSNP in the 3′ UTR of Kallikrein-related peptidase 3 ( KLK3 ) created a binding site for miR-3162-5p. Here we investigated the miR-3162-5p–KLK interaction and the clinical implication of miR-3162-5p in PCa. METHODS: We tested the role of miR-3162-5p in PCa etiology using IncuCyte live-cell imaging and anchorage-independent growth assays. The effect of miR-3162-5p on KLK and androgen receptor (AR) expression was measured by RT-quantitative (q)PCR and target pulldown assays. KLK3 proteolytic activity was determined by DELFIA ® immunoassay. Mass spectrometry identified pathways affected by miR-3162-5p. miR-3162-5p expression was measured in clinical samples using RT-qPCR. RESULTS: miR-3162-5p affected proliferation, migration, and colony formation of LNCaP cells by regulating the expression of KLK2–4 and AR by direct targeting. KLK3 protein expression was regulated by miR-3162-5p consistent with lower KLK3 proteolytic activity observed in LNCaP-conditioned media. KLK/AR pulldown and mass spectrometry analysis showed a potential role of miR-3162-5p in metabolic pathways via KLK/AR and additional targets. Increased miR-3162-5p expression was observed in prostate tumor tissues with higher Gleason grade. CONCLUSIONS: Our study provides an insight into possible involvement of miR-3162-5p in PCa etiology by targeting KLKs and AR. It highlights clinical utility of miR-3162-5p and its interactive axis as a new class of biomarkers and therapeutic targets for PCa.